From network language to academic-scientific writing: descriptive study in students of education - Quiles Cabrera, María del Carmen (Círculo de Lingüística Aplicada a la Comunicación, 2021)
In this publication, we begin by reflecting on the concept of scientific language in literature, which also have their own specialized lexicon and a discursive code. Thus, we ask ourselves how our university students have developed their competences in this sense, when reading and writing spaces have evolved according to ICT and the digital world. Learners move between the language of the networks and an academic context that requires a change of register to which they are rarely accustomed. Thus, we carried out an empirical research based on a case study: a group of 126 students from the Primary Education Degree of the University of Almería, by proposing an open questionnaire around the “definition” of a lexicon corpus specific related to the area of Didactics of Language and Literature. This way, we highlight the lexical competence of the group in question and we are able to describe the most characteristic features when using the “definition” as a communicative situation of the academic-scientific field.